90x^2+15x-30 (hope this helps)
Answer:
y² - (K- 2)y + 2k +1 = 0
equal roots means D=0
D= b^2 - 4ac
a=1, b= (k-2), c= 2k+1
so,
(k-2)^2 - 4(1)(2k+1) = 0
=> k^2 +4 - 8k -4 = 0
=> k^2 -8k = 0
=> k^2 = 8k
=> k= 8k/k
=> k = 8
Therefore the answer is k= 8
Hope it helps........
Answer:
(-4,14)
(which you already choose)
Step-by-step explanation:
All it is asking is to plug the given x values into the equation (which are 0, 2, 4) and see what you get for y.
4y - 2x =16
4y - 2 (0) = 16
4y = 16
y = 4
4y - 2 (2) = 16
4y - 4 = 16
4y = 20
y = 5
4y - 2 (4) = 16
4y - 8 = 16
4y = 24
y = 6
so D
Answer:
(x - 3)(x + 7)
Step-by-step explanation:
x^2 + 4x - 21
=> x^2 + 7x - 3x - 21
=> x(x + 7) -3(x + 7)
=> (x + 7)(x - 3)